(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Current trend in global development is to manage national economies sustainably, but significant challenge is measuring progress. There is a need for studies that can help to monitor if national economy develops sustainably or not. The aim of this study is to assess the main trends in sustainable economic development in Estonian and Latvian economies. Literature review, regression and correlation analysis are applied for data analysis in this research. The results allow to conclude that Estonia and Latvia have not reached the turning point in sustainable development when larger GDP is produced with using fewer amounts of natural resources and generating less waste (falling Footprint). Both countries have similar sustainable development trends, excluding temp of increase in the number of population.